Pendampingan Kepada Masyarakat Dalam Renovasi Masjid Daarut Taqwa - Soegoto, Eddy Soeryanto; Natalia, Tri Widiati; Sutisnawati, Yayah; Maryati, Mari; Soegoto, Dedi Sulistiyo (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2020)
ABSTRACT Daarut Taqwa Mosque is one of the Jami mosques which is very crowded with various religious activities, such as Friday prayers, Tarawih prayers and Islamic studies routinely carried out by DKM Daarut Taqwa Mosque. The more activities of congregants, DKM Daarut Taqwa Mosque seeks to renovate the mosque to fulfill and accommodate all the congregant who come. The purpose of this article is to show community service activities carried out by the UNIKOM Team in assisting the renovation of the Daarut Taqwa Mosque and assistance in designing the interior and exterior image concept of the mosque. The method of implementation is the design approach, design ideas based on activities, behavior, and activities that take place at the Daarut Taqwa Mosque. The results obtained from the assistance of the construction of the Daarut Taqwa Mosque are the Community Concept as the main concept of the Daarut Taqwa mosque. This concept is to strengthen the